2007
DOI: 10.1002/er.1366
|View full text |Cite
|
Sign up to set email alerts
|

Influence of massive heat-pump introduction on the electricity-generation mix and the GHG effect—Belgian case study

Abstract: SUMMARYTo evaluate the environmental impact of massive heat-pump introduction on greenhouse gas (GHG) emissions, dynamic simulations of the overall electricity-generation system have been performed for Belgium. The simulations are carried out with Promix, a tool that models the overall electricity-generation system. For comparison, three heating devices are considered, namely conventional boilers, heat pumps and electrical resistance heating. The introduction of electric heating at the expense of classic heati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…5 Floor heating is only considered in the buildings built after 1990, for which the nominal heating power allows applying a low temperature heat emission systems, such as floor heating [39]. In each case, the heat pump also supplies the domestic hot water demand (DHW), which is stored either in a 200 l or 300 l tank at 50 C, depending on the maximum daily demand.…”
Section: Heating Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Floor heating is only considered in the buildings built after 1990, for which the nominal heating power allows applying a low temperature heat emission systems, such as floor heating [39]. In each case, the heat pump also supplies the domestic hot water demand (DHW), which is stored either in a 200 l or 300 l tank at 50 C, depending on the maximum daily demand.…”
Section: Heating Systemsmentioning
confidence: 99%
“…For instance, Reynders et al [4] found that due to passive solar gains the space heating demand is mostly lower at times when PV panels are generating electricity; hence, a carbon intensity strongly affected by PV might not be a good measure for the CO 2 emissions related to space heating. Second, the electricity demand associated with a massive heat pump introduction could correlate with peak electricity demand, increasing the need for peak power capacity [5]. Finally, these published methods for accounting CO 2 emissions are unable to predict the emission reduction and peak shaving potential when heat pumps participate in active demand response (ADR) programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Rinne and Syri [10] performed a life cycle assessment study to calculate CO2 emissions from HPs and combined heat and power (CHP) production in Finland. Luickx et al [11] focused on the impact of the power generation and CO2 emissions in Belgium when integrating large amounts of HPs. Mathiesen and Lund [12] used EnergyPlan [7] to compare how suitable several technologies are to integrate fluctuating wind power in the energy system.…”
Section: Introductionmentioning
confidence: 99%
“…However, the COP for the HPs was assumed to be constant. A constant COP for HPs was also assumed in other studies that looked at different ways of integrating more RES at national or city level, such as in Trondheim, Norway [15], in Geneva, Switzerland [16], in Belgium [17], in Finland [18] or in Denmark [19][20][21].…”
Section: Introductionmentioning
confidence: 99%